Electrophysiological properties of dual atrioventricular nodes in patients with right atrial isomerism. Issue 5 (November 1995) - Wu, M. H.; Lin, J. L.; Wang, J. K.; Chiu, I. S.; Young, M. L.
Abstract : There are reports that in right atrial isomerism the conduction system has paired sinus nodes and paired atrioventricular nodes. Electrophysiological studies were performed in two patients with right atrial isomerism. One patient had a delta wave on the surface electrocardiogram without tachycardia attacks. The other, who did not have manifest pre-excitation, had recurrent narrow QRS tachycardia. Electrophysiological studies suggested the presence of dual atrioventricular nodes. Only unidirectional atrioventricular or ventriculoatrial conduction was demonstrated for these dual atrioventricular nodes even after infusion of isoprenaline. It is suggested that unidirectional conduction may be a common property of the dual atrioventricular nodes in right atrial isomerism and that the absence of retrograde ventriculoatrial conduction protects the patients against tachycardia.